2015
DOI: 10.1080/1369183x.2015.1081055
|View full text |Cite
|
Sign up to set email alerts
|

Love thy neighbour? Exploring prejudice against ethnic minority groups in a divided society: the case of Northern Ireland

Abstract: Northern Ireland has seen a rise in racially motivated crimes and incidents reported to police in recent years and, although this has been accompanied by intensified media coverage, this phenomenon has been the subject of relatively little research. The purpose of this study is to evaluate empirically three theories that have been proposed to explain prejudice towards ethnic minorities in Northern Ireland; economic self-interest, social contact, and 'sectarianism as racism'. Using the 2013 Northern Ireland Lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 35 publications
(36 reference statements)
3
19
0
Order By: Relevance
“…This finding indicates that when it comes to the impact of sectarianism on attitudes towards other minorities, Northern Ireland is indeed still a special case. Consistent with other research and with findings on other countries (McLaren 2003;Hayes and Dowds 2006;Hewstone et al 2006;Tam et al 2007;Frølund Thomsen 2012;McKee 2015), we found that regular contact (at least once a week) with minorities makes individuals less likely to endorse negative attitudes towards them. The findings support contact theory (Pettigrew 1998;Brown and Hewstone 2005;Tam et al 2009).…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…This finding indicates that when it comes to the impact of sectarianism on attitudes towards other minorities, Northern Ireland is indeed still a special case. Consistent with other research and with findings on other countries (McLaren 2003;Hayes and Dowds 2006;Hewstone et al 2006;Tam et al 2007;Frølund Thomsen 2012;McKee 2015), we found that regular contact (at least once a week) with minorities makes individuals less likely to endorse negative attitudes towards them. The findings support contact theory (Pettigrew 1998;Brown and Hewstone 2005;Tam et al 2009).…”
Section: Resultssupporting
confidence: 81%
“…This concurs with researchers who found negativity towards ethnic minorities to be predominantly a phenomenon of the urban male Protestant working-class (Hewstone et al 2006;McVeigh and Rolston 2007;Tam et al 2007;Knox 2011;McKee 2015).…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations